Planting density and training system in young orchads of 'Cerrito' peach - Boeira, Rita Carla; Barradas, Carlos I. N.; Koller, Otto Carlos (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was established in 1982, at Guaíba, RS, southern Brazil, in a latheritic soil, to evaluate first and second crops (1983/84 and 1984/85) of peach trees Prunus persica (L.) Batsch cv. Cerrito, in three spaces: 5 m x 2 m, 5 m x 3 m and 5 m x 4 m, and trained at the open center, "Spindelbusch" and irregular palmette with oblique arms systems. The yield per tree showed a direct relationship to planting density, at the "spindelbusch", in 1983/84; at the open center system, an inverse behavior occurred in 1984/85.The yield per hectare kept a direct relationship of the planting densities with the "spindelbusch" and palmette, which were more precocious on denser plantings, showing a predominance of extra fruit crop in the total crop. The mean fruit weight increased in the second harvest (1984/85), due to the low cropping. The mean weight and the number of fruits were not influenced by treatments.